Phase diagram of the restricted primitive model: charge-ordering instability - Patsahan, O.V.; Mryglod, I.M. (Condensed Matter Physics, 2004)
We study the phase behaviour of the restricted primitive model (RPM) using a microscopic approach based on the method of collective variables with a reference system. Starting from the Hamiltonian of the RPM we derive the functional of the grand partition function given in terms of the two collective variables: the collective variables ρk and ck describing fluctuations of the total number density and charge density, respectively. Within the framework of the Gaussian approximation we found the boundary of stability with respect to fluctuations of the charge density. It is shown that due to the approximated character of the theory the boundary of stability is very sensitive to the particular choice of the long-range part of potential inside the hard core. This point is discussed in more detail.